PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING DENGAN TEKNIK KANCING GEMERINCING TERHADAP AKTIVITAS DAN HASIL BELAJAR - Umah, Sofwatul; Enawaty, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aims of this research are to differentiate student’s activities and learning outcome that taught using problem solving learning with buttoned clashing technique and the students who were taught without using problem solving learning with buttoned clashing technique, and determine the influence of problem solving learning with buttoned clashing technique toward learning outcomes the eleven grade students of SMAN 1 Rasau Jaya on the solubility and solubility. Types of the research is Quasy experiment with nonequivalent control group design research’s program. The sample was taken by saturated sampling technique. Data were analyzed using U-Man Whitney test. The result of the students activity showed that Asymp.Sig (2-tailed) value is 0,000 (α = 5%), and the students learning outcomes showed Asymp.Sig (2-tailed) value is 0,002 (α = 5%). This finding showed that the activities and students learning outcomes’ differences between the students who were taught by problem solving learning with buttoned clashing technique and the students who were taught without using the model. The use of problem solving learning with buttoned clashing technique gave influence 21,77% to the improvement of the students learning outcomes.Keywords : Problem Solving, Buttoned Clashing Technique, Activities, Learning Outcomes